2017
DOI: 10.1038/modpathol.2016.177
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA profiling of low-grade glial and glioneuronal tumors shows an independent role for cluster 14q32.31 member miR-487b

Abstract: Low-grade (WHO I–II) gliomas and glioneuronal tumors represent the most frequent primary tumors of the central nervous system in children. They often have a good prognosis following total resection, however they can create many neurological complications due to mass effect, and may be difficult to resect depending on anatomic location. MicroRNAs have been identified as molecular regulators of protein expression/translation that can repress multiple mRNAs concurrently through base pairing, and play an important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 64 publications
(69 reference statements)
1
31
0
Order By: Relevance
“…miR‐21 and members of the miR‐17‐92 cluster) or down‐regulation of microRNAs with reported oncosuppressive effects in various settings. The latter included miR‐218 , miR‐124 , miR‐487b and miR‐139‐5p .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…miR‐21 and members of the miR‐17‐92 cluster) or down‐regulation of microRNAs with reported oncosuppressive effects in various settings. The latter included miR‐218 , miR‐124 , miR‐487b and miR‐139‐5p .…”
Section: Resultsmentioning
confidence: 99%
“…Thus far, however, the research conducted on these noncoding RNA species in pLGGs has been largely descriptive. Moreover, the conclusions that can be drawn from these studies are frequently limited by the small number of cases analysed , the inclusion of high‐grade gliomas besides pLGGs or the inclusion of adult patients .…”
Section: Discussionmentioning
confidence: 99%
“…Among the predicted candidate miRNAs, miR‐129 serves as a biomarker and tumor suppressor in gastric cancer, breast cancer, and endometrial cancer . In addition, miR‐192 expression is abnormally downregulated in subependymal giant cell astrocytoma . Herein, we selected miR‐129 as an object for further experiments and speculated that miR‐129 might target CDK1 and iASPP to modulate TAp63‐mediated Burkitt lymphoma cells proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Gattolliat and colleagues in 2011 showed that miRNA cluster can be useful to differentiate the low‐risk neuroblastoma from high‐risk ones. The microarray and qRT‐PCR analysis showed the downregulation of members of 14q32.31 miRNA cluster in high risk group when compared with low risk neuroblastoma (Ames, Yuan, Vizcaíno, Yu, & Rodriguez, ). Thus, expression analysis of miR‐487b and miR‐410 could be useful for stratification of neuroblastoma into high‐risk and low‐risk types and relapse in favorable neuroblastoma (Gattolliat et al, ).…”
Section: Clustered Mirna and Prognostic Significancementioning
confidence: 99%